Communication in Knowledge Transfer Management - Pitra, Zbyněk; Zaušková, Anna (Communication Today, 2025)
Innovations try to change the status quo, which is why markets resist them! A market’s hostility to innovations becomes stronger when market players are interconnected; each player will switch to a new product or service only when s/he believes others will do so, as well. To be successful, innovators have to realize system-wide switch of their business behavior to create environment, where many would adopt their innovations and believe they are better off because of it. It is feasible only if innovators master the process of knowledge transfer within their innovation activities. More than 50% of promising and good prepared innovation activities fail. Not due to organizations’ weaknesses in technology or organization, but due to their inability to handle properly the social and psychological aspects of processes which deal with the innovation’s solution. Therefore the organization’s executives must fully understand how technologies, people’s competencies, and internal processes in architecture together influence internal communication during the knowledge transfer that leads to the innovation solutions. It is a unifying vision of final innovation’s market launch that gives coherence to the plenty of creative ideas from different sources which gives an organizational sense to the idea exchange during internal communication within the knowledge transfer processes‘ performance. The paper deals with methods that will assure such knowledge transfer’s optimal efficiency.